Never just friends - Esguerra, Mina V. (Mandaluyong City Anvil, 2015)
It's too easy to fall in love with Jake. Don't do it.Lindsay and Jake have loved each other (as friends) since their senior year in college, and she made sure they didn't become more than that. The guy now known as Jacob Berkeley, star of a wildly successful TV show, was always too much for her. Too handsome, too many questionable hookups, too restless. Also sensitive, fun, and genuinely caring. She's his emergency contact, his "zombie apocalypse buddy," his holiday dinner companion.They've kept up this low-maintenance friendship for years, surviving graduation, their new careers, her move to New York City to work as an environment consultant. But then, days before a big climate change conference, he shows up, with big news. Jake wants to pick up what he never managed to finish in college. He wants to save forests again, work in environmental research - and he wants her.Don't fall in love with Jake...Why again?
Keywords: Romance fiction, Philippine (English).